2015
DOI: 10.1186/s12863-015-0290-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and genomic prediction of breeding values for fatty acid composition in subcutaneous adipose and longissimus lumborum muscle of beef cattle

Abstract: BackgroundIdentification of genetic variants that are associated with fatty acid composition in beef will enhance our understanding of host genetic influence on the trait and also allow for more effective improvement of beef fatty acid profiles through genomic selection and marker-assisted diet management. In this study, 81 and 83 fatty acid traits were measured in subcutaneous adipose (SQ) and longissimus lumborum muscle (LL), respectively, from 1366 purebred and crossbred beef steers and heifers that were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 79 publications
(85 reference statements)
9
40
2
7
Order By: Relevance
“…Other studies in sheep underlined the higher accuracy of genomic methods compared with the pedigree-based approach for milk and meat production traits (Daetwyler et al, 2012;Legarra et al, 2014;Baloche et al, 2014). Moreover, GS studies carried out in beef cattle on muscle FA composition reported for some of FA also investigated in this study a similar pattern of GEBV accuracy (Chen et al, 2015;Chiaia et al, 2017;Zhu et al, 2017).…”
Section: Accuracy Of Ebv and Gebv Predictionssupporting
confidence: 73%
See 1 more Smart Citation
“…Other studies in sheep underlined the higher accuracy of genomic methods compared with the pedigree-based approach for milk and meat production traits (Daetwyler et al, 2012;Legarra et al, 2014;Baloche et al, 2014). Moreover, GS studies carried out in beef cattle on muscle FA composition reported for some of FA also investigated in this study a similar pattern of GEBV accuracy (Chen et al, 2015;Chiaia et al, 2017;Zhu et al, 2017).…”
Section: Accuracy Of Ebv and Gebv Predictionssupporting
confidence: 73%
“…In dairy sheep, the molecular basis of FA has been investigated by candidate gene (Crisà et al, 2010;Moioli et al, 2012), and QTL detection approaches. Genomic selection studies for FA compositions are limited to beef cattle (Uemoto et al, 2011;Chen et al, 2015;Zhu et al, 2017) and meat sheep (Rovadoscki et al, 2018). One of the main advantages of GS over traditional selection is that, once a reference population with both phenotypic and genotypic records has been settled, breeding values of animals without their own phenotypes can be predicted with a reasonable accuracy (Meuwissen et al, 2001;Hayes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Of the five major enriched molecular and cellular biological functions, lipid metabolism was common to all the four traits, with synthesis of lipids including triglycerides appearing as a very important subfunction or process. Lipid metabolism has also been identified as an enriched molecular process for feed efficiency traits in beef cattle in several transcriptome studies [63][64][65]. In finishing beef cattle, deposition of fat requires more energy than protein because protein synthesis is energetically more efficient than fat synthesis [12,66].…”
Section: Genetic Network Compared With Rnaseqmentioning
confidence: 99%
“…For example, carnosine, anserine and taurine have been suggested to be associated with health benefits (Hipkiss, 2009;Huxtable, 1992). Whereas genetic parameters for fatty acid compositions in beef have been reported relatively frequently (Chen et al, 2015;Inoue, Kobayashi, Shoji, & Kato, 2011;Nogi, Honda, Mukai, Okagaki, & Oyama, 2011;Onogi et al, 2015;Saatchi et al, 2013), reports on genetic parameters for other meat components, such as free amino acids and peptides, have been still limited (Mateescu et al, 2012;Sakuma et al, 2016). Thus, our first aim was to investigate genetic parameters for 51 meat components, including free amino acids, peptides and fatty acid compositions in a large Japanese Black cattle population.…”
Section: Introductionmentioning
confidence: 99%
“…Although sex differences in genetic variance are generally small in economic traits, large differences occasionally have been reported in the growth and carcase traits (Garrick, Pollak, Quaas, & Van Vleck, 1989;St alhammar & Philipsson, 1997). Genetic analyses of meat compositions are usually conducted in one sex (Inoue et al, 2011;Sevane et al, 2013) or treat sex as fixed effect (Chen et al, 2015;Nogi et al, 2011;Onogi et al, 2015;Saatchi et al, 2013;Sakuma et al, 2016). Hence, sex differences in genetic parameters and gene-sex interactions remain unstudied in any breed.…”
Section: Introductionmentioning
confidence: 99%